Whole-Genome Duplication and Purifying Selection Contributes to the Functional Redundancy of Auxin Response Factor (ARF) Genes in Foxtail Millet (Setaria italica L.) - You Chen; Bin Liu; Yujun Zhao; Wenzhe Yu; Weina Si (International Journal of Genomics)
Auxin response factors (ARFs) play crucial roles in auxin-mediated response, whereas molecular genetics of ARF genes was seldom investigated in Setaria italica, an important crop and C4 model plant. In the present study, genome-wide evolutionary analysis of ARFs was performed in S. italica. Twenty-four SiARF genes were identified and unevenly distributed on eight of the nine chromosomes in S. italica. Duplication mode exploration implied that 13 SiARF proteins were originated from whole-genome duplication and suffered purifying selection. Phylogeny reconstruction of SiARFs by maximum likelihood and neighbor-joining trees revealed SiARFs could be divided into four clades. SiARFs clustered within the same clade shared similar gene structure and protein domain composition, implying functional redundancy. Moreover, amino acid composition of the middle regions was conserved in SiARFs belonged to the same clade. SiARFs were categorized into either activators or repressors according to the enrichment of specific amino acids. Intrinsic disorder was featured in the middle regions of ARF activators. Finally, expression profiles of SiARFs under hormone and abiotic stress treatment not only revealed their potential function in stress response but also indicate their functional redundancy. Overall, our results provide insights into evolutionary aspects of SiARFs and benefit for further functional characterization.